2016
DOI: 10.1161/strokeaha.115.010920
|View full text |Cite
|
Sign up to set email alerts
|

Role of Erythrocyte CD47 in Intracerebral Hematoma Clearance

Abstract: Background and Purpose Enhancing hematoma clearance through phagocytosis may reduce brain injury after intracerebral hemorrhage (ICH). In the current study, we investigated the role of CD47 in regulating erythrophagocytosis and brain injury after ICH in nude mice. Methods This study was in two parts. First, male adult nude mice had an intracaudate injection of 30-µl saline, blood from male adult wild type (WT) mice or blood from CD47 knockout (CD47 KO) mice. Second, mice had an intracaudate injection of 30-µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 41 publications
0
63
0
Order By: Relevance
“…Recent research has studied microglia/macrophage activation and polarization in several neurological conditions, including brain ischemia [10, 11, 1618]. However, the polarized microglia/macrophage activation after ICH has not been well studied [36, 37]. The present study reveals the time course of polarized microglia/macrophage activation after ICH, which should provide a solid basis for further investigation to microglia/macrophage-mediated inflammatory injury and repair after ICH.…”
Section: Discussionmentioning
confidence: 58%
“…Recent research has studied microglia/macrophage activation and polarization in several neurological conditions, including brain ischemia [10, 11, 1618]. However, the polarized microglia/macrophage activation after ICH has not been well studied [36, 37]. The present study reveals the time course of polarized microglia/macrophage activation after ICH, which should provide a solid basis for further investigation to microglia/macrophage-mediated inflammatory injury and repair after ICH.…”
Section: Discussionmentioning
confidence: 58%
“…Phagocytosis of erythrocytes by microglia/macrophages has a role in hematoma clearance after ICH 7 . The current study examined the natural time course of CD47 expression in the hematoma in a swine ICH model and found that CD47 levels in the clot decrease with time.…”
Section: Discussionmentioning
confidence: 99%
“…On normal RBCs, CD47 inhibits phagocytosis via interaction with an inhibitory receptor, signal regulatory protein alpha (SIRPα), on phagocytes. Our recent study showed that CD47 on RBCs has a role in clot removal following ICH 7 .…”
Section: Introductionmentioning
confidence: 92%
“…In the third part, WT or PAR-1 KO mice received an intracerebral injection of thrombin (0.4U) in saline or saline alone (n=7 per group). Based on our prior study on the variance in ICH-induced brain swelling in mice 14 , we estimated that an n=7 per experimental group would be able to detect a 50% reduction in brain swelling with greater than 80% power. All mice were euthanized at 24 hours or 72 hours after T2-weighted magnetic resonance imaging (MRI) and behavioral testing.…”
Section: Methodsmentioning
confidence: 99%
“…Brain swelling calculation was based upon seven every other sections whose center was the anterior commissure layer. The value was: volume of (ipsilateral hemisphere- contralateral hemisphere)/volume of contralateral hemisphere×100 % 12, 14 .…”
Section: Methodsmentioning
confidence: 99%